The Influence of Leadership and Work Environment on Organizational Commitment and Employee Performance of PT. Bank Mega, Tbk Regional Makassar during the Covid-19 pandemic - Gary Leonard Hendrik; Djabir Hamzah; Andi Reni (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to determine the influence of leadership and work environment on organizational commitment and employee performance at PT Bank Mega, Tbk Regional Makassar during the Covid-19 pandemic. This research was conducted at Bank Mega Regional Makassar by taking information from permanent employees who have worked for more than 3 (three) years using a questionnaire, with a total sample of 158 employees. The data were analyzed using a quantitative approach and processed using the SPSS version 22 application. The results of this study indicate that leadership has no significant effect on employee performance during the Covid-19 pandemic, in contrast to the work environment and organizational commitment which have a significant effect on employee performance during the Covid pandemic. -19. This shows that during the Covid-19 pandemic, companies should pay more attention to the quality of the employee's work environment and focus on the process of increasing employee organizational commitment to the company.